A teremtő rombolás szerepe a vállalati termelékenység alakulásában Magyarországon - Gábor Békés; László Halpern; Balázs Muraközy (Hungarian Academy of Sciences, Institute of Economics, 2010)
– In this paper we investigate the relationship between productivity growth and firm dynamics using firm-level data between 1992 and 2006. Theories emphasising firm-level heterogeneity show that industry-level productivity may not only increase as a consequence of increasing within-firm efficiency, but also because of the quicker growth of more efficient firms, i.e. creative destruction. With analytical tools from recent literature we show that increasing firm-level efficiency was the main factor behind industry-level productivity growth in Hungary in this period, but creative destruction also played an important role.
Keywords: D24; L25; O47; 330; creative destruction; productivity; heterogeneity; Produktivität; Schätzung; Ungarn